"Choose-a-size" control in the synthesis of sucrose based urea and thiourea macrocycles. Issue 33 (9th August 2018) - Łęczycka-Wilk, Katarzyna; Ulatowski, Filip; Cmoch, Piotr; Jarosz, Sławomir
Abstract : High yield synthesis of either monomeric or dimeric sucrose-based macrocycles is just a matter of choice – flow or batch synthesis. Abstract : Highly efficient synthesis of monomeric and dimeric thiourea macrocycles with a per- O -benzylated sucrose scaffold is reported. Application of flow synthesis results in exclusive formation of a monomer in 79% yield. Batch synthesis provides two isomeric dimers in 85% yield. Dimers are capable of anion binding via two thiourea groups acting cooperatively.